Influência do tratamento térmico de austenitização sobre a microestrutura do revestimento e substrato em blanks patchwork de um aço ao Boro laminado a frio com revestimento Zn-Fe para conformação a quente - Joao Luiz Costa Carvalho (2018)
The demand for coated boron steels for auto parts, processed by direct hot forming, has tripled in the last three years in Mercosur, reaching almost 60 kt / year. Cold rolled boron steel, coated with Zn-Fe or galvannealed (GA), offers a very efficient cathodic protection of the parts and a stable behavior in the welding process. This steel was developed recently by Usiminas, receiving the commercial name of USIGALGAPHS1500. The effect of austenitizing heat treatment on the coating and substrate microstructures were evaluated in this study, for blank patchworks with total thickness of 3.0 mm and 3,4 mm. The results showed that the coating evolution after direct hot forming under the conditions evaluated, were equivalent in the internal and external faces of the patchwork blanks, prevailing in the coating a compact solid solution with a mass percent Zn composition between 20% and 40%. The substrates evaluated, in the external regions of bending specimens were free of cracks. Thicker blanks, such as 3.4 mm, may require furnace times higher than 340 s to achieve a more efficient quenching of the part. Furnace temperatures of 900°C and 920°C led to with a more homogeneous surface appearance.